The performance of aluminium to carbon fibre composite bonded joints in motorsport applications - Loftus,D.; Found, M. S.; Yates, J. R. (Sports Engineering, 1999)
Race car manufacturers have been adhesive bonding composite monocoques for more than 15 years. The latest Grand Prix cars have more than 60 bonded joints and there is increasing interest in structural bonding of dissimilar materials. However, static strength and fatigue durability data for designing adhesive bonded joints between metallic and composite components in a race car chassis are likely to be over-conservative when generated using standard single lap joint bonded specimens. Experimental work has been carried out using modified single lap joint specimens to generate fatigue and static strength design data for the case of an aluminium alloy bonded to carbon fibre composite using a cold cured epoxy adhesive. Test specimens were modified by changing the ratio of the width of the carbon fibre to aluminium adherends in the range from 1:1 to 2:1 to provide a better representation of the case of small metal components being attached to larger composite structures. The mean static strength of the standard single edge lap specimens with a 1:1 width ratio of adherend was 22% lower than the specimens with wider carbon fibre composite adherends. Modifying the aluminium adherend in the 2:1 width ratio specimens by changing the end from square to semicircular increased the mean static strength by a further 23%. The 2:1 width ratio specimens also had substantially increased fatigue lives compared with the standard 1:1 width ratio specimens. At a nominal shear stress range of 12 MPa and R ratio of 0.06, the mean fatigue life of the wider specimens was increased by almost a factor of five. Examination of the failed specimens supported the hypothesis that the edges of the bonded area are the dominant factor in the failure process. The practical outcome of this work is to question the use of standard test geometries when generating strength and durability data for the design of adhesive bonded components for motorsport applications.